ANALISIS KEMAMPUAN PEMODELAN MATEMATIS PESERTA DIDIK PADA MATA PELAJARAN FISIKA - Desy Kumala Sari; Uke Ralmugiz (MEGA: Jurnal Pendidikan Matematika, 2020)
This research aims to describe the students ' ability to menyelesaiakan problems regarding mathematical modeling. This research is quantitative research with the survey method. The research was conducted in Kupang City with 152 SMA Negeri Kupang students as a research subject. The instrument used in this research is a mathematical modeling ability test, which consists of 15 items of mathematical modeling questions. Analyze data using the help of the Quest software. Results show the average student's ability in mathematical modeling is moderate, but there are only two categories of moderate (58%) and low (42%), while none have high proficiency (0%).